Tailoring Tomato (Solanum lycopersicum L.) Traits to Microclimates: A Multilocation Evaluation of Yield and Quality Responses in Western Ethiopia - Usman Mohammed Ali; Desalegn Negasa Soresa; Tilahun Wondimu Fufa (Scientifica)
Tomato (Solanum lycopersicum L.) is a crucial crop for food security and income generation in Western Ethiopia. However, unsuitable cultivar choices and misalignment between genotype and microclimate conditions often constrain its productivity. This study aimed to evaluate the performance of eight national tomato cultivars and one local landrace across diverse microclimates in Western Ethiopia during the 2022/2023 off-season cropping period. A randomized complete block design with three replications was employed to assess growth, yield, and quality parameters at two locations: Bako Tibe and Gambella Tare. The results revealed significant genotype–environment interactions affecting various traits, underscoring the necessity for microclimatic adaptation in tomato cultivation. Cochoro emerged as a high-yielding cultivar, achieving marketable fruit yields of 91.5 t/ha at Bako and 84.28 t/ha at Gambella Tare, while Komto (43 t/ha at Bako Tibe) and Geli-Lema (42.2 t/ha at Gambella Tare) exhibited the lowest yields. Melka-Salsa demonstrated superior fruit quality, particularly in ascorbic acid content (26.30 mg/100 g), while Cochoro had the lowest (12.81 mg/100 g). A strong positive correlation (r = 0.998∗∗) was identified between total marketable fruit yield and fruit weight per plant, suggesting potential targets for future breeding efforts. This study highlights the critical role of genotype–environment interactions in optimizing tomato production across microclimates in Western Ethiopia. These findings provide valuable information for farmers and stakeholders to select the most suitable cultivars, enhancing yields and improving farmer incomes. Future research should prioritize expanded genotype–environment interaction studies, breeding programs targeting yield components and stress resilience traits, and the development of location-specific agronomic packages integrating optimized irrigation, nutrient management, and climate-smart pest control strategies.